AKURASI SINYAL TRANSISI DALAM TULISAN ARGUMENTATIF: STUDI KUALITATIF DESKRIPTIF - Lisbeth Sirait; Chatrine Meylani Chen (Prodi Sastra Inggris UKI, 2026)
This research examines the categories and precision of transitional devices utilized by first-semester English Literature students at Universitas Kristen Indonesia in their argumentative compositions. Informed by the theoretical perspectives of Oshima and Hogue (2006), Halliday and Hasan (1976), and Hyland (2007), the study employs a descriptive qualitative methodology to scrutinize 28 students’ essays. The results indicate a primary dependence on additive and contrastive transitions, coupled with infrequent application of causal and temporal connectors. Although students exhibit a rudimentary grasp of fundamental linkers such as “and,” “also,” and “however,” their vocabulary diversity and grammatical accuracy are notably restricted. Instances of inaccuracy encompass superfluous repetition, colloquial expressions, and sparse incorporation of sophisticated transitional phrases. (